(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Crash performance is imperative to ensure safety of vehicle. A major challenge in the design and optimization of vehicle crash systems is the high computing costs needed for crash analysis. It is imperative that energy-absorbing structural principles can be introduced and optimized at the early stages of vehicle design in order to improve crash efficiency by creative and optimized vehicle architecture. Through developing rapid modelling strategies, this potential can be maximized. In this paper modelling approaches are investigated using Finite Element Method for one application. Description for energy absorption structures are studied and implemented into new user defined model description for an explicit Finite Element Crash Solver. The simplified energy absorbing structure is verified using Finite Element Models